Understanding Nursing Assistants' Experiences of Caring for Older People in Pain: The Australian Experience - Holloway, Kristi; McConigley, Ruth (Elsevier Science, 2009)
This study examined the experiences of nursing assistants (NAs), who have worked with older people in residential aged care facilities (RACFs) who are in pain, to ascertain the role that NAs play in the pain management process. A descriptive, exploratory qualitative approach was used to examine NAs' experiences. Six NAs employed in three RACFs in regional Western Australia participated in the study. In-depth interviews focusing on the NAs experiences of caring for older people in pain were conducted. This study provided an understanding of the care needs of older residents in pain and illuminated the role of NAs in the pain management process. The central role that NAs play in RACFs was highlighted, as were the responsibilities associated with pain management. Nursing assistants may be responsible for initiating and implementing pain management treatments for older residents. This is outside the scope of practice for NAs; therefore, it is imperative that the preparation of NAs give them adequate knowledge to perform this role. As well, it may be timely to consider regulation of this large group of workers who are performing clinical tasks in RACFs.